DESKRIPSI PELAKSANAAN PEMBELAJARAN TEMATIK BERBASIS ONLINE PADA KELAS V SDN 05 PONTIANAK KOTA - Liberta Kaunang; Tahmid Sabri; Rio Pranata (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to obtain subjective information about how to describe theimplementation of online-based thematic learning. Qualitative researchusing descriptive methods, namely seeing the reality on the ground as it isand as it is. Participants in the study were fifth grade students and classteachers at SDN 05 Pontianak Kota, which consisted of 30 students. Datacollection techniques using triangulation techniques, the data collectiontools used in this study were assisted by observation sheets, interviewsheets, documentation. The results showed that: (1) learning was carriedout online using the whatsapp application, (2) learning facilities usingcellphones and computers, (3) limited internet quota, students who did nothave cellphones, (4) students had difficulty understanding the material.given by the teacher and did not meet his classmates. The conclusion ofonline-based thematic learning in class V SDN 05 Pontianak City has apositive impact on students because it can avoid the transmission of theCovid-19 virus, but the limited internet quota and other facilities plusstudents' difficulties in understanding the material pose a challenge toeducators in applying thematic learning methods.Keywords: Learning, Online Based, Thematic